2010
DOI: 10.1089/end.2009.0630
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Vesicourethral Anastomosis Healing After Robot-Assisted Laparoscopic Radical Prostatectomy: Lessons Learned from Three Techniques in 1900 Patients

Abstract: TR of the continence mechanism optimizes vesicourethral anastomosis healing and hastens early continence return after RALP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 43 publications
5
35
0
2
Order By: Relevance
“…Our results showed clinically significant anastomotic leak rates of 3.7% in group 1 vs. 4.9% in group 2. These are comparable with the rates reported in other series, which ranged from 0.8 to 17% of cases [5,11,26]. Similarly, the rate of bladder neck stricture, which in this study was 3.7% in group 1 and 1.2% in group 2, remains in line with the previously published rates [11,12].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed clinically significant anastomotic leak rates of 3.7% in group 1 vs. 4.9% in group 2. These are comparable with the rates reported in other series, which ranged from 0.8 to 17% of cases [5,11,26]. Similarly, the rate of bladder neck stricture, which in this study was 3.7% in group 1 and 1.2% in group 2, remains in line with the previously published rates [11,12].…”
Section: Discussionsupporting
confidence: 93%
“…It has to be noted that in this study, we preserved the bladder neck using our own technique in all patients to avoid a potential bias that could have affected the analysis of continence outcomes [13,14]. Sparing of bladder neck has been associated with better functional outcomes after surgery due to a lower risk of urethral injury and bladder neck stricture [24,25,26]. It has been suggested that bladder neck preservation may compromise oncological outcomes by increasing the risk of positive surgical margins.…”
Section: Discussionmentioning
confidence: 99%
“…Tablo (5,6,19,20), hastanın mevcut komorbiditeleri (7), alt üriner sistem semptomlarının şiddeti ve ameliyat öncesi erektil disfonksiyon varlığı (5,8); RYLP geçiren hastalardaki kontinansı doğru orantılı olarak bozan diğer anlamlı faktörler olarak bildirilmiştir.…”
Section: Rylp Sonrası İdrar Kaçırma Oranları Ve İdrar Kaçırmayı öNgörunclassified
“…Tan ve ark. 'larının 1600 hastayı içeren serilerinde total rekonstrük-siyon grubunda anlamlı avantaj sağlandığı gösterilmiştir (19). Atuğ ve ark.…”
Section: Posterior Ve Anterior Rekonstrüksiyonunclassified
“…For this reason, reconstruction of the posterior rhabdosphincter to restore anatomic relations is one approach to improve urinary outcomes [70][71][72] . Based on an improved understanding of the male continence mechanism, anatomic restoration of the vesicourethral junction has also been postulated to improve early continence outcomes [ 42,73,74 ] . Moreover, the fascial investments of the rhabdosphincter fuse anteriorly with the pubourethral, i.e., puboprostatic ligamentsextensions of the arcus tendineus, and provide stabilization to the continence mechanism [ 42,49 ] .…”
Section: Surgery and Urinary Incontinencementioning
confidence: 99%